Melanocyte and Melanoma Cell Activation by Calprotectin - Stephanie H. Shirley; Kristine von Maltzan; Paige O. Robbins; Donna F. Kusewitt (Journal of Skin Cancer)
Calprotectin, a heterodimer of S100A8 and S100A9, is a proinflammatory cytokine released from ultraviolet radiation-exposed keratinocytes. Calprotectin binds to Toll-like receptor 4, the receptor for advanced glycation end-products, and extracellular matrix metalloproteinase inducer on target cells to stimulate migration. Melanocytes and melanoma cells produce little if any calprotectin, but they do express receptors for the cytokine. Thus, keratinocyte-derived calprotectin has the potential to activate melanocytes and melanoma cells within the epidermis in a paracrine manner. We examined the ability of calprotectin to stimulate proliferation and migration in normal human melanocytes and melanoma cells in vitro. We first showed, by immunofluorescence and quantitative RT-PCR, that the melanocytic cells employed expressed a calprotectin receptor, the receptor for advanced end-products. We then demonstrated that calprotectin significantly enhanced proliferation, migration, and Matrigel invasion in both normal human melanocytes and melanoma cells. Thus, calprotectin is one of the numerous paracrine factors released by ultraviolet radiation-exposed keratinocytes that may promote melanomagenesis and is a potential target for melanoma prevention or therapy.